Indonesian-English code mixing in Raditya Dikaâs Manusia Setengah Salmon - Wulandari, Santika (Journal on English as a Foreign Language (JEFL), 2016)
This study was aimed at investigating Indonesian-English code mixing in Raditya Dikaâs Manusia Setengah Salmon, particularly to find out the word classes of the code mixing, the meaning of the code mixing, the dominant use of the code mixing, and the reasons for using the code mixing. Content analysis in qualitative approach was applied in this study. To collect the data, it was through data collection, data reduction, data display, and conclusion drawing. The results showed that there are 65 sentences or utterances consisted English nouns as code mixing. They were categorized into countable nouns (87.69%), uncountable nouns (3.08%), abstract nouns (6.15%), concrete nouns (1.54%), and plural nouns (1.54%). Among them, countable nouns are more dominant than others. Also, three kinds of translating process found are: borrowing consisted of 25 sentences, literal consisted of 14 sentences, and adaptation consisted of 28 sentences.